PENGEMBANGAN MODUL PEMROGAMAN DASAR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KOMPUTASI DI MAN 5 AGAM - Fikri Muhammad; Dedi Efendi; Riri Okra (Kampus Akademik Publiser, 2023)
Abstract. In process in basic programming subjects still using Powerpoint media. Scratch module based learning media is a module that explains about the Scratch programming language. The purpose of this study is to study the differences in student learning outcomes before and using modules and to determine students' thinking skills using modules. This research method is research and development (R&D) with one group pretest postest design research design is the design used in this study and uses the ADDIE development model (Analysis, Design, Development, implementatiion, & Evaluation). Assessment Results from Dr. Scratch get the average value of students' ability to think Competency after using the Scratch module is 9.74 for questions number 1, 10.61 the average for questions number 2, 9.77 average for questions number 3, 14.00 averages average for question number 4. Can refute students' thinking abilities good.